Stabilizing Economic Growth Since Covid-19 Pandemic: Evidence from OIC Country - Ariyani, Diyah; Waharini, Faqiatul Mariya (Universitas Muhammadiyah Yogyakarta, 2024)
This research investigated how the government stabilized its economy in terms of government spending during the global crisis of the COVID-19 pandemic. This study also tried to identify whether there is a difference in the amount of government spending from the aspect of government spending before the global crisis of the COVID-19 pandemic and after the global crisis of the COVID-19 pandemic. The data covered all members of the Organization of Islamic Cooperation (OIC) spread across 4 continents. In looking at which factors affect economic growth, multiple linear regression is used, and a comparative test is carried out by conducting a Different Paired Sample T-Test. After testing in this study, researchers found that there were differences in government policies in terms of government spending carried out before the global crisis of the COVID-19 pandemic and after the global crisis of the COVID-19 pandemic. The independent variables used in the study had a significant positive influence except for the population. This research also shows that the government's efforts to maintain economic growth by increasing government spending are policies that have been implemented globally. This research is expected to provide recommendations for policies that can be implemented by the government in an effort to stabilize the economy, including increasing per capita income, increasing the human development index, and increasing trade activities abroad and domestically.